3 - Economic Reforms and the Malian Economy: 10.4314/ad.v27i1.22151 - Dialla, Basga Emile (Africa Development, 2002)
In the late 1 980s Mali embarked on a comprehensive programme of economic reforms. Reform policy has been successful in dismantling some components of the patronage system put in place in the country after independence, in curbing the worst macroeconomic imbalances, and in reorienting public expenditures in favour of the social sectors and longer-term growth. The devaluation of the CFA franc, the deepening of the integration process in West Africa, and the HIPC initiative contributed, to various extents, in improving the economic situation and growth performance in Mali. In order to make growth more sustained and better balanced, reform policy needs to put greater emphasis on measures that improve incentives for private investment and human capital accumulation. This is necessary so that the relatively high growth that was experienced by Mali during the second half of the 1990s becomes more than just a short-lived episode.